Undergraduate Research Experience (URE): A New Dimension in Curricular Redesign - Kumbhar, Sanjay R.; Attar, A. C.; Telsang, M. T. (Journal of Engineering Education Transformations, 2018)
Research experience for undergraduates is of great importance not only for conducting research on a topic that has impact on a current research activity, but also as a tool to enhance undergraduate education. For the engineering technology students, research experiences allow them to carry out in-depth study of engineering concepts, while emphasizing hands-on experiences and practical applications. Participating in funded research projects strengthens the student's resume, and fulfills the requirements of present day employers, who demand sound engineering skills in their employees. This paper highlights the importance of undergraduate research experience with its curriculum design, expected outcomes, methodologies to be followed and implementation plan. Also barriers and strategies to overcome have also been discussed. Finally model of this at RIT has been presented.